Purposeful heading in youth soccer: a review - Wahlquist, V. E.; Kaminski, T. W. (Sports Medicine, 2021)
Recent public concern over the short- and long-term effects of repetitive head impacts (RHI) associated with purposeful heading in soccer has led researchers to study a multitude of variables related to this important aspect of the game. Of particular interests are the effects of soccer heading in the youth population (= 13 years old) whose brains are undergoing rapid development. We conducted a review on youth soccer heading that includes purposeful heading frequency, head impact biomechanics, head injuries, clinical outcomes, and modifying factors. We have concluded that youth soccer players head the ball at a low frequency that typically increases with age and with a finding that boys head the ball more often than girls do. Interestingly, although girls head the ball less frequently than boys do, they tend to sustain higher head impact magnitudes. Head injuries are more likely to occur in girls versus boys and during games because of contact with another player. Clinical outcome measures of concussion are often utilized to study the effects of soccer heading, in both field and laboratory environments. Immediately following soccer heading, youth often report having a headache and demonstrate some deficits in balance measures. Modifying factors that may benefit soccer players participating in purposeful heading activities include stronger neck musculature, wearing headgear, and the use of mouthguards. Research involving youth soccer players needs to be expanded and funded appropriately to better understand the consequences of RHI in both the short and long term.